A longitudinal investigation of Aβ, anxiety, depression, and mild cognitive impairment. Issue 10 (8th December 2021) - Pink, Anna; Krell‐Roesch, Janina; Syrjanen, Jeremy A.; Vassilaki, Maria; Lowe, Val J.; Vemuri, Prashanthi; Stokin, Gorazd B.; Christianson, Teresa J.; Kremers, Walter K.; Jack, Clifford R.; Knopman, David S.; Petersen, Ronald C.; et al.
Abstract: Introduction: We investigated the longitudinal relationship between cortical amyloid deposition, anxiety, and depression and the risk of incident mild cognitive impairment (MCI). Methods: We followed 1440 community‐dwelling, cognitively unimpaired individuals aged ≥ 50 years for a median of 5.5 years. Clinical anxiety and depression were assessed using Beck Anxiety and Depression Inventories (BAI, BDI‐II). Cortical amyloid beta (Aβ) was measured by Pittsburgh compound B positron emission tomography (PiB‐PET) and elevated deposition (PiB+) was defined as standardized uptake value ratio ≥ 1.48. We calculated Cox proportional hazards models with age as the time scale, adjusted for sex, education, and medical comorbidity. Results: Cortical Aβ deposition (PiB+) independent of anxiety (BAI ≥ 10) or depression (BDI‐II ≥ 13) increased the risk of MCI. There was a significant additive interaction between PiB+ and anxiety (joint effect hazard ratio 6.77; 95% confidence interval 3.58–12.79; P  = .031) that is, being PiB+ and having anxiety further amplified the risk of MCI. Discussion: Anxiety modified the association between PiB+ and incident MCI.